The use of dual growing rods to correct spinal deformity secondary to a low-grade spinal cord astrocytoma - Kuhn, Elizabeth N. (J Surg Case Rep, 2015)
Pediatric intramedullary spinal cord astrocytomas are rare, and the majority are low grade, typically carrying a low risk of mortality, but a high risk of morbidity. Quality of life is, therefore, an important consideration in treating concomitant progressive kyphoscoliosis. Compared with fusion-based spinal stabilization, fusionless techniques may limit some complications related to early instrumentation of the developing spine. Another consideration is the timing of radiation therapy relative to both spinal maturity and spinal instrumentation. To date, there have been no reports of the use of a fusionless technique to treat spinal deformity secondary to an intramedullary spinal cord tumor. Herein, we report the use of fusionless spinal stabilization with dual growing rods in a boy with low-grade spinal cord astrocytoma after radiation therapy.